Evaluasi Mekanisme Pelaksanaan Retribusi Pelayanan Parkir di Tepi Jalan Umum Kota Pontianak - B103141065, Tiya Nurfauziah (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
Public area parking service retribution is one of the sources in increasing the original local government revenue, also, the number of vehicles that keep increasing, but the number of vehicles is not proportional to the realization of revenue from the parking sector due to certain factors that cause less optimal regional revenue of the parking sector. The purpose of this study is to determine whether the mechanism of the implementation of parking service retribution on the of public areas of Pontianak City and  to determine the factors that contribute to the effectiveness of the implementation of parking service retributions on the public areas of Pontianak City.The research method used in this research is descriptive qualitative analysis. With the analysis tools such as interviews, observation, literature study, and document review. The informant from this research are Department of Transportation of Pontianak City and parking officers as the parking practitioners on the field.The result of this research is the income of retribution of parking service on the public areas has been categorized as effective, but not optimal yet in its implementation because of lack of firmness of information from local government to the society especially the owner of business concerning parking collection system which in practice managed by two Regional Work Unit, the absence of SOP of the collection so that the parking coordinator has full rights regarding the deposit from the parking officer and the Department of Transportation who is not aware of the actual amount of deposit received by the parking coordinator so that the coordinator takes advantage of the parking space as a personal gain and the leakage of income of public parking retribution cause the realization of income of public roadside parking service retribution is not yet optimal and it also affects the local government revenue, the lack of supervision from the Department of Transportation in the field regarding which of the parking officers are still active and which are  not, so that the data owned  is not valid because it only recorded who ever signed up as a parking oficer. Keywords: Evaluation, Parking Service Retribution on the Public Road, Local Government Revenue